2015
DOI: 10.1509/jmr.13.0165
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Effects of Buyers and Sellers on Search Advertising Revenues in Business-to-Business Electronic Platforms

Abstract: Platform companies such as Alibaba.com increasingly rely on search advertising as a revenue source. This study examines (1) the direct effect of new and existing buyers and sellers on platform advertising revenue, (2) their indirect effect through two intermediary performance variables (buyer's click rate and seller's click price), and (3) how the effects differ between launch and mature stages of the search advertising service. Unique data collected from a leading transactional business-to-business electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 49 publications
0
35
0
4
Order By: Relevance
“…To survive, platform owners may have to reach critical mass on both sides of the ecosystem early [58,59], meaning that a platform owner can first explore the size of the installed base and then exploit the potential value of that base. A penetration strategy works for this purpose by charging a low price early to attract customers and then raising rates over time [38].…”
Section: Pricingmentioning
confidence: 99%
“…To survive, platform owners may have to reach critical mass on both sides of the ecosystem early [58,59], meaning that a platform owner can first explore the size of the installed base and then exploit the potential value of that base. A penetration strategy works for this purpose by charging a low price early to attract customers and then raising rates over time [38].…”
Section: Pricingmentioning
confidence: 99%
“…Researchers from USA and China have studied the direct effect of new and existing buyers and sellers on platform advertising revenue, their indirect effect through two intermediary performance variables (buyer's click rate and seller's click price), and how the effects differ between launch and mature stages of the search advertising service (Fang et al, 2015). Fang and his colleagues by using unique data collected from a leading transactional business-to-business electronic companies have found that companies increasingly rely on search advertising as a revenue source and suggest that new buyers click on more search advertisements than existing buyers, especially after the firm's buyers and sellers have learned and adapted to the service (mature stage).…”
Section: Theoretical Findingsmentioning
confidence: 99%
“…Attracting new buyers also has a greater effect on click rate and price, especially in the mature stage. Fang et al (2015) by using cost data from the platform have examined the economic returns of attracting new and existing buyers and sellers with respect to advertising revenue). Aspects of how online firms market to change their business model successfully by moving from free to fee have also several findings (Pauwels and Wiss, 2008).…”
Section: Theoretical Findingsmentioning
confidence: 99%
“…Other literature confirmed information as being the primary utility of B2B publications for the audience to do their work (Jeffers, 1989;Randle, 2003;Van der Wurff, 2002a, 2002b. B2B media service products such as advertising and events generate awareness, cause responses, enable transactions (Chamblee & Sandler, 1992;Fang, Huang & Palmatier, 2015), and establish business-to-business connections and interactions (Mair, 2013;Mair and Thompson, 2009;Medjahed, Benatallah, Bouguettaya, Ngu & Elmagarmid, 2003). All these must be based on the pre-condition of connectivity utility with which advertisers connect with their audiences, and companies with their clients and stakeholders.…”
Section: Introductionmentioning
confidence: 97%